Human Neutrophils Kill Bacillus anthracis. (PLoS Pathogens, 2005)
Bacillus anthracis spores cause natural infections and are used as biological weapons. Inhalation infection with B. anthracis, the etiological agent of anthrax, is almost always lethal, yet cutaneous infections usually remain localized and resolve spontaneously. Neutrophils are typically recruited to cutaneous but seldom to other forms of anthrax infections, raising the possibility that neutrophils kill B. anthracis. In this study we infected human neutrophils with either spores or vegetative bacteria of a wild-type strain, or strains, expressing only one of the two major virulence factors. The human neutrophils engulfed B. anthracis spores, which germinated intracellularly and were then efficiently killed. Interestingly, neutrophil killing was independent of reactive oxygen species production. We fractionated a human neutrophil granule extract by high-performance liquid chromatography and identified alpha-defensins as the component responsible for B. anthracis killing. These data suggest that the timely recruitment of neutrophils can control cutaneous infections and possibly other forms of B. anthracis infections, and that alpha-defensins play an important role in the potent anti-B. anthracis activity of neutrophils.